2020
DOI: 10.1155/2020/6027405
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Lymphocyte Ratio (NLR) Reflects Myocardial Inhomogeneities in Hemodialyzed Patients

Abstract: Introduction. Cardiovascular diseases (CVDs) are a leading cause of death in chronically hemodialyzed (HD) patients. In this group, inflammation exerts significant impact on the prevalence of CVD morbidity and mortality. Spatial QRS-T angle is an independent and strong predictor of CV events, including sudden cardiac death (SCD), both in general population and HD patients. Pathogenesis of widened QRS-T angle is complicated and is not well established. Objectives. The study is aimed at evaluating whether inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…The spatial QRS-T angle, obtained from the basic 12-lead ECG, is the angle between the vectors of the QRS loops and the T-wave, which indirectly reflects ventricular depolarization and repolarization. An abnormally wide spatial QRS-T angle was defined as > 116° for females and > 130° in males [24,25]. We did not observe significant changes in the the QRS-T angle, which may confirm that a single session in a cryochamber does not significantly affect depolarization and repolarization.…”
Section: Discussionmentioning
confidence: 47%
“…The spatial QRS-T angle, obtained from the basic 12-lead ECG, is the angle between the vectors of the QRS loops and the T-wave, which indirectly reflects ventricular depolarization and repolarization. An abnormally wide spatial QRS-T angle was defined as > 116° for females and > 130° in males [24,25]. We did not observe significant changes in the the QRS-T angle, which may confirm that a single session in a cryochamber does not significantly affect depolarization and repolarization.…”
Section: Discussionmentioning
confidence: 47%
“…In fact, recently, it has been reported that HALP can indicate the malnutrition and systemic inflammatory state of chronic diseases, and it turns out to be a relevant outcome symbol for different tumors. [9][10][11][12][13] Interestingly, there are some improved indicators based on blood laboratory tests, such as Neutrophil-Lymphocyte Ratio and Monocyte-lymphocyte ratio, [21,22] which are often mentioned in the analysis of the appraisal of nutritional and inflammatory condition in dialysis subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that HSP27 may contribute to the reduction of LDL oxidative modification, thus demonstrating that HSP27 plays a protective role in atherogenesis [ 27 , 34 , 35 ]. In addition, our previous study showed that inflammation may play a role in the pathogenesis of myocardial inhomogeneities in HD patients [ 36 ], and HSP27 is known to be involved in modulating inflammation. It is worth emphasizing that the results of ROC analysis revealed that the HSP27 cut-point value predicting abnormal QRS-T angle was similar to the HSP27 value predicting the occurrence of contrast-induced nephropathy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%